2013
DOI: 10.1007/s00222-013-0457-0
|View full text |Cite
|
Sign up to set email alerts
|

Rotational symmetry of self-similar solutions to the Ricci flow

Abstract: Let (M,g) be a three-dimensional steady gradient Ricci soliton which is non-flat and \kappa-noncollapsed. We prove that (M,g) is isometric to the Bryant soliton up to scaling. This solves a problem mentioned in Perelman's first paper.Comment: Final version, to appear in Invent. Mat

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
155
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 24 publications
5
155
0
Order By: Relevance
“…This is a sequel to our earlier paper [4], in which we proved a uniqueness theorem for the three-dimensional Bryant soliton. Recall that the Bryant soliton is the unique steady gradient Ricci soliton in dimension 3, which is rotationally symmetric (cf.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…This is a sequel to our earlier paper [4], in which we proved a uniqueness theorem for the three-dimensional Bryant soliton. Recall that the Bryant soliton is the unique steady gradient Ricci soliton in dimension 3, which is rotationally symmetric (cf.…”
Section: Introductionmentioning
confidence: 76%
“…[6]). In [4], it was shown that the threedimensional Bryant soliton is unique in the class of κ-noncollapsed steady gradient Ricci solitons: Theorem 1.1 (S. Brendle [4]). Let (M, g) be a three-dimensional complete steady gradient Ricci soliton which is non-flat and κ-noncollapsed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an interesting question to classify ancient solutions and Ricci solitons. We refer to [10], [11], [12], [14] for some recent progress in this direction.…”
Section: Introductionmentioning
confidence: 99%